Describing the Students’ Grammatical Errors on Spoken English - Imanuel Kamlasi (ELT-Lectura, 2019)
This present study describes the students’ grammatical errors on spoken English based on the classifications of errors refer to Dulay, Burt and Krashen’s theories. Qualitative method was used in the study. Oral test was used as the research instrument. There were 25 participants of English education study program of Timor University who were chosen randomly as the research sample. The Tape Video Recording (TVR) was used to gain data of spoken English. There were five techniques in analyzing the data: transcription, codification, classification, analyses and discussion. The results of data analyses revealed that omission presented 40,87% of errors. Then; addition presented 31,74% and misformation presented 15%. The misorderning was categorized as the lowest score with 12,30%. In linguistic category; the data showed that verb was categorized as the highest errors which presented 19% of errors. The next error was preposition which presented 17%. Then pronouns category presented 14% of errors. The conjunction and article categories presented 11% of errors on spoken English. The singular/plural and negation categories presented 10% of errors for each category. The lowest error of linguistic category was word order which presented 8% errors. The findings showed that the students still make errors on linguistic category on spoken English. There was a phenomenon in this finding that the students tend to use verb-ing instead of using verb-1 in the spoken English. They dispose to add and omit any linguistic category unconsciously when they speak.